MODERN LEARNING IMPROVEMENTS SUPPORTED BY IT SOLUTIONS – SLIDO CASE STUDY FOR BETTER ENGAGEMENT - STOJAKOVIĆ, Dušan (Annals of Spiru Haret University. Economic Series, 2022)
According to a study published by UNESCO at the beginning of the coronavirus pandemic, about 84% of the world’s population studying some of the educational programs (including formal education through primary, secondary and higher education, and university undergraduate and postgraduate studies) is affected by prevention and social distances. Experts estimate that such disability and absenteeism will cause a significant and noticeable lack of theoretical knowledge and practical skills at the global level for several generations, the study of which was lacking in the process of switching from physical to online teaching and digital study of the material. for studying in the physical environment of a classroom, amphitheatre, laboratory or similar educational facilities. One of the ways to partially alleviate this process of not studying the entire prescribed material and accredited curricula on time relies on more intensive application of IT technologies, innovations and solutions, with a special focus on increasing the degree of student involvement in active learning. One of such IT solutions is SLIDO, an online software, primarily aimed at use for business purposes but certainly and unstoppably finding its way to improve education. This paper aims to explore potentials of increasing students’ engagement through IT solutions like SLIDO.